2012
DOI: 10.1186/1472-6963-12-337
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral health providers' perspectives of delivering behavioral health services in primary care: a qualitative analysis

Abstract: BackgroundCo-located, collaborative care (CCC) is one component of VA’s model of Integrated Primary Care that embeds behavioral health providers (BHPs) into primary care clinics to treat commonly occurring mental health concerns among Veterans. Key features of the CCC model include time-limited, brief treatments (up to 6 encounters of 30 minutes each) and emphasis on multi-dimensional functional assessment. Although CCC is a mandated model of care, the barriers and facilitators to implementing this approach as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
40
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 25 publications
1
40
0
Order By: Relevance
“…As in prior research, practices in our study worked to balance their ideal approach to integrated care delivery with the resources and infrastructure at hand. 10,19,21 ACT and IWS practices that aspired to staff and schedule BHCs to enable real-time delivery of integrated care via warm handoffs secured resources to expand BHC staffing, dealt with billing structures that reinforced scheduling patterns for delivering traditional mental health care during 50-minute appointments, and put in the effort required to change care delivery in their organization. In addition, local availability and capabilities of the BHC workforce, who may be trained in a referral model with 50-minute prescheduled therapy appointments, may constrain what is feasible to implement, at least initially.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As in prior research, practices in our study worked to balance their ideal approach to integrated care delivery with the resources and infrastructure at hand. 10,19,21 ACT and IWS practices that aspired to staff and schedule BHCs to enable real-time delivery of integrated care via warm handoffs secured resources to expand BHC staffing, dealt with billing structures that reinforced scheduling patterns for delivering traditional mental health care during 50-minute appointments, and put in the effort required to change care delivery in their organization. In addition, local availability and capabilities of the BHC workforce, who may be trained in a referral model with 50-minute prescheduled therapy appointments, may constrain what is feasible to implement, at least initially.…”
Section: Discussionmentioning
confidence: 99%
“…20 Research on practices that aspired to have BHCs provide brief treatment for both mental health and behavioral health concerns at the point of care found that implementation depends on an interaction between described ideals, locally available resources, and decisions regarding resource deployment. 10,21 Despite these apparent challenges with accessing BHC services, little is known about the relationship between staffing, scheduling, and a primary care practice's approach to integrated care.…”
mentioning
confidence: 99%
“…In our prior qualitative work, we found that PC-MHI providers tended to develop local models of CCC that were dependent upon both their level of knowledge regarding population-based models of mental health care and local resource limitations, such as provider staffing levels and physical layout of the clinic [26]. Thus, both provider and contextual factors came together to determine the degree of provider fidelity.…”
Section: Original Researchmentioning
confidence: 91%
“…The professional training obtained by social workers may serve as a good foundation to becoming highly adherent PC-MHI providers. Social workers may also have an advantage over other providers because of their emphasis on providing holistic care to patients and knowledge of how to navigate large health care systems to connect patients to a wide range of services [26]. The most adherent cluster was also associated with a higher level of clinic integration as measured by the Level of Integration Measure.…”
Section: Original Researchmentioning
confidence: 97%
“…Nevertheless, one detailed study based on a survey of mental healthcare professionals in the VA system working in primary care facilities gives an enlightening account. 4 The fourteen "behavioral health providers" (BHPs) who responded represented 48% of the BHPs in that particular regional VA network; they were asked about their perceived role as co-located, collaborative care providers. Significantly, none of the respondents was a psychiatrist.…”
Section: Psychotherapymentioning
confidence: 99%